Conducting original research for your library - Gerrity, Caitlin; Lanning, Scott (New York : Bloomsbury Libraries Unlimited, 2024)
"A concise manual for professionals in the field, this book helps librarians master the skills to conduct, interpret, and analyze their own original research"--
Includes bibliographical references and index.
Keywords: Library science -- Research -- Methodology